Volume 3C: Heat Transfer 2013
DOI: 10.1115/gt2013-94345
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tip Clearance Gap and Exit Mach Number on Turbine Blade Tip and Near-Tip Heat Transfer

Abstract: It is important to be able to accurately predict the heat transfer distribution over a component when designing the turbine section of an engine. The gas temperature exiting the combustor in many gas turbine engines is above the melting temperature of turbine components. These high gas temperatures can quickly degrade components and cause failure. A detailed heat transfer study on these turbine components is an important input when developing ways to cool them. One such important component is the gas turbine b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Anto et al. 13 investigated the effects of tip clearance height and exit Mach number on heat transfer coefficient distribution on the tip surface using a transient infrared thermography technique, and showed that the leakage flow imposes a relatively significant sheer effect (flow migration) in a larger tip gap case, which was consistent with the fact that a larger tip gap implies that more leakage flow would enter the tip clearance gap.…”
Section: Introductionmentioning
confidence: 84%
“…Anto et al. 13 investigated the effects of tip clearance height and exit Mach number on heat transfer coefficient distribution on the tip surface using a transient infrared thermography technique, and showed that the leakage flow imposes a relatively significant sheer effect (flow migration) in a larger tip gap case, which was consistent with the fact that a larger tip gap implies that more leakage flow would enter the tip clearance gap.…”
Section: Introductionmentioning
confidence: 84%
“…Within the figure, color variations denote tip surface heat flux variations, and greyscale variations denote flow density gradient distributions which were employed in these studies utilized squealer configurations [57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72], partial squealer configurations [61,64,69], and winglet configurations [73,74]. Smooth blade tips were employed by Thorpe et al [75], Green et al [59], Key and Arts [62], O'Dowd et al [76,77], Wheeler et al [78], Zhang et al [55,56], Shyam et al [79], Atkins et al [80], Wheeler and Saleh [70], Anto et al [81], Virdi et al [68], Wheeler and Sandberg [82], Li et al [65], Zhang et al [83], Zhang and He [84], Wang et al [69], Zhou [71], Jung et al [61], Gao et al [85], and Kim et al [64]. Most of these investigations (which involved experimental measurements) employed annular or linear cascades with stationary blades.…”
Section: Interactions Which Included Thermal Transport and Convectivementioning
confidence: 99%
“…Park et al 2 and Acharya et al 3 pointed out that for flat tip and squealer, heat transfer near tip leading edge is higher due to leakage flow reattachment, while heat transfer on tip cavity floor decreases with cavity depth increasing. Anto et al 4 experimentally studied effects of the clearance height and exit Mach number on tip heat transfer characteristics. It was found that tip heat transfer coefficient increases 3% with clearance height increasing from 0.9% to 1.8%, while tip heat transfer coefficient increases 39% with exit Mach number changing from 0.85 to 1.05.…”
Section: Introductionmentioning
confidence: 99%